2005
DOI: 10.1038/nature03412
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the onset of locking in the Peru–Chile trench with GPS and acoustic measurements

Abstract: The subduction zone off the west coast of South America marks the convergence of the oceanic Nazca plate and the continental South America plate. Nazca-South America convergence over the past 23 million years has created the 6-km-deep Peru-Chile trench, 150 km offshore. High pressure between the plates creates a locked zone, leading to deformation of the overriding plate. The surface area of this locked zone is thought to control the magnitude of co-seismic release and is limited by pressure, temperature, sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
131
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(144 citation statements)
references
References 22 publications
5
131
0
Order By: Relevance
“…Black arrows are velocity vectors of the Nazca plate at the convergence margin with the South American plate (Chlieh et al, 2011). 87 sites surveyed from the period 1993-2003 in Peru (Chlieh et al, 2011). These data include interseismic seafloor deformations measurements obtained offshore Lima city from a deployment of seafloor acoustic transponders and inland GPS receivers (Gagnon et al, 2005). The ISC model is based on the assumption that convergence between the Nazca and South American plates is dominantly accommodated along the megathrust including 4 mm=yr of back-arc shortening absorbed at the subandean fold and thrust belt regions (Chlieh et al, 2011).…”
Section: Isc Model and Scenario Earthquakementioning
confidence: 99%
“…Black arrows are velocity vectors of the Nazca plate at the convergence margin with the South American plate (Chlieh et al, 2011). 87 sites surveyed from the period 1993-2003 in Peru (Chlieh et al, 2011). These data include interseismic seafloor deformations measurements obtained offshore Lima city from a deployment of seafloor acoustic transponders and inland GPS receivers (Gagnon et al, 2005). The ISC model is based on the assumption that convergence between the Nazca and South American plates is dominantly accommodated along the megathrust including 4 mm=yr of back-arc shortening absorbed at the subandean fold and thrust belt regions (Chlieh et al, 2011).…”
Section: Isc Model and Scenario Earthquakementioning
confidence: 99%
“…An alternative interpretation of the result of Gagnon et al (2005) is that the shallow part is not locked, but looks apparently locked due to the interplate locking in a deeper part of the plate boundary. Whether this difference can be observed by geodetic observations on the seafloor, or not, is an important problem.…”
Section: Some Important Results Of Gpsa Observations Before 2011mentioning
confidence: 99%
“…One of the critical reasons why the giant earthquake had not been suspected is the lack of information on the locking in the shallow part of the plate boundary. While GPSA observations by Gagnon et al (2005) in the Peru-Chile subduction zone suggested that the shallow part of the plate boundary is locked, few repeating earthquakes had been observed on the shallow plate boundary off Miyagi (Uchida and Matsuzawa, 2011). A low degree of locking was estimated there, and GPSA observations in the area had been delayed.…”
Section: Some Important Results Of Gpsa Observations Before 2011mentioning
confidence: 99%
See 2 more Smart Citations